2016
DOI: 10.1097/igc.0000000000000827
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Metastases in Patients With Cervical Carcinoma

Abstract: The present study describes the largest series of patients with CNSm from CC; this rare complication should be suspected in patients with CC who present with headache, ataxia, cranial nerve palsy, visual disturbance, altered mental status, focal weakness, or other neurological symptom, without other plausible explanation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…It is worth noting that almost half of the patients (up to 40%) with intracranial metastasis from CC had advanced stage disease [7, 16]. In another report of 27 patients, 21 (77.8%) had stage IIB disease or more advanced stages of disease [29]. Most patients with brain metastasis also developed recurrence at extracranial sites, including in the lungs (39%), bones (16%), and abdomen/pelvis (16%) [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that almost half of the patients (up to 40%) with intracranial metastasis from CC had advanced stage disease [7, 16]. In another report of 27 patients, 21 (77.8%) had stage IIB disease or more advanced stages of disease [29]. Most patients with brain metastasis also developed recurrence at extracranial sites, including in the lungs (39%), bones (16%), and abdomen/pelvis (16%) [7].…”
Section: Discussionmentioning
confidence: 99%
“…Records from 81 patients with uterine cancer metastasis to the brain in Japan showed a median OS of 7 months (95% CI 4–10) [48]. In another study, the mean survival was 8.2 months after central nervous system metastasis was discovered [29]. It has been suggested that the treatment modality, particularly combined therapies, is significantly related to OS [49].…”
Section: Discussionmentioning
confidence: 99%
“…The interval between the primary diagnosis and BMs was available for 216 patients [11,[14][15][16]18,[20][21][22][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][43][44][45]47,[50][51][52][53][55][56][57][59][60][61][62]64,65,67,72,73,75,76,80,83], and ranged from −1 week to 386 months (median 24 months). A literature review published in 2012 reported that the median interval between the diagnosis of CC and BMs was 18 months [148].…”
Section: Prevalence and Clinical Characteristicsmentioning
confidence: 99%
“…The initial symptoms of BMs from CC may be nonspecific, and may include headaches (45.6%), syncope or seizures (14.0%), ataxia (11.8%), nausea/vomiting (11.0%), hemiparesis (10.3%), visual disturbance including diplopia (8.8%), generalized or extremity weakness (8.8%), altered mental status (6.6%), dizziness (5.1%), confusion (5.1%), speech impairment (5.1%), paresthesia, facial twitching, tinnitus, tremor and hemiballismus [11,14,18,20,21,[23][24][25][26]28,29,[31][32][33][34][35][37][38][39][42][43][44][45]47,[50][51][52][55][56][57][58]60,61,[63][64][65]76,80,81]. Intracranial edema resulted in papilledema due to the increased intracranial pressure, which is a common sign of a brain tumor [64,148]. These symptoms and signs are the same as those of other brain-occupying lesions.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation